TRAINING YOUNG TEACHERS FOR WORKING WITH PARENTS IN MORAL EDUCATION OF UPPER PRESCHOOL CHILDREN: THEORETICAL ARE ASPECTS - Zalizniak, Alla (European Science, 2023)
The research considers the problem of training young teachers for working with parents in moral education of upper-preschool children, analyzing the essense and state of the problem researched in the pedagogical theory and practice of higher education. Th